FGF6 and FGF9 regulate UCP1 expression independent of brown adipogenesis - Shamsi, Farnaz; Xue, Ruidan; Huang, Tian Lian; Lundh, Morten; Liu, Yang; Leiria, Luiz O.; Lynes, Matthew D.; Kempf, Elena; Wang, Chih-Hao; Sugimoto, Satoru; Nigro, Pasquale; Landgraf, Kathrin; et al. (Nature communications, 2020)
Uncoupling protein-1 (UCP1) plays a central role in energy dissipation in brown adipose tissue (BAT). Using high-throughput library screening of secreted peptides, we identify two fibroblast growth factors (FGF), FGF6 and FGF9, as potent inducers of UCP1 expression in adipocytes and preadipocytes. Surprisingly, this occurs through a mechanism independent of adipogenesis and involves FGF receptor-3 (FGFR3), prostaglandin-E2 and interaction between estrogen receptor-related alpha, flightless-1 (FLII) and leucine-rich-repeat-(in FLII)-interacting-protein-1 as a regulatory complex for UCP1 transcription. Physiologically, FGF6/9 expression in adipose is upregulated by exercise and cold in mice, and FGF9/FGFR3 expression in human neck fat is significantly associated with UCP1 expression. Loss of FGF9 impairs BAT thermogenesis. In vivo administration of FGF9 increases UCP1 expression and thermogenic capacity. Thus, FGF6 and FGF9 are adipokines that can regulate UCP1 through a transcriptional network that is dissociated from brown adipogenesis, and act to modulate systemic energy metabolism. Uncoupling protein-1 (UCP1) plays a central role in energy dissipation in brown adipose tissue. Here the authors show that FGF6 and FGF9 induce UCP1 expression in adipocytes and preadipocytes, via modulation of a transcriptional network that is dissociated from brown adipogenesis.